The cauchy-poisson waves in an inviscid rotating stratified liquid. (1990) - Debnath, Lokenath; Guha, Uma B.; Basu, Manjusri
Abstract : Based upon the Boussinesq approximation, an initial value investigation is made of the axisymmetric free surface flows generated in an inviscid rotating stratified liquid of infinite depth by the prescribed free surface disturbance. The asymptotic analysis of the integral solution is carried out by the stationary phase method to describe the solution for large time and large distance from the source of the disturbance. The asymptotic solution is found to consist of the classical free surface gravity waves and the internal-inertial waves.